2015
DOI: 10.1002/poc.3478
|View full text |Cite
|
Sign up to set email alerts
|

Ruthenium(III) catalysed and uncatalysed oxidative mechanisms of methylxanthine drug theophylline by copper(III) periodate complex in alkali media: a comparative approach

Abstract: The kinetics of oxidation of methylxanthine drug, theophylline (TP), by diperiodatocuprate(III) (DPC) has been investigated in the absence and presence of ruthenium(III) (Ru(III)) as homogeneous catalyst in alkaline medium at a constant ionic strength of 0.21 mol dm−3 spectrophotometrically. The reaction exhibits 1:4 stoichiometry ([TP] : [DPC]) in both the cases. The order of the reaction with respect to [DPC] was unity, while the order with respect to [TP] was less than unity over the concentration range stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 28 publications
1
1
0
Order By: Relevance
“…It was observed that the reaction exhibited an order of negative fraction with respect to [IO 4 − ], less than unit order in DG and alkali concentrations (Table 1). In view of the retarding effect of periodate, the active species of DPC have been proposed as [Cu(H 2 IO 6 )(H 2 O) 2 ], which was also observed in earlier report, [ 25 ] and the mechanism befitting the obtained results was proposed (Scheme 1). In aqueous alkaline medium, a diaquomonoperiodato copper (III) complex (MPC) (in Equation 5) was produced due to substitution of bidentate ligand [H 3 IO 6 2− ] of DPC by water molecules, and its formation was important in the present study.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…It was observed that the reaction exhibited an order of negative fraction with respect to [IO 4 − ], less than unit order in DG and alkali concentrations (Table 1). In view of the retarding effect of periodate, the active species of DPC have been proposed as [Cu(H 2 IO 6 )(H 2 O) 2 ], which was also observed in earlier report, [ 25 ] and the mechanism befitting the obtained results was proposed (Scheme 1). In aqueous alkaline medium, a diaquomonoperiodato copper (III) complex (MPC) (in Equation 5) was produced due to substitution of bidentate ligand [H 3 IO 6 2− ] of DPC by water molecules, and its formation was important in the present study.…”
Section: Discussionsupporting
confidence: 55%
“…Thus, [Cu(H 3 IO 6 ) (H 2 IO 6 )] 2− is the soluble copper (III) periodate complex in the employed pH conditions, also supported by the earlier work. [ 25 ]
…”
Section: Discussionmentioning
confidence: 99%
“…The presence of hydrated form of ruthenium(III) chloride in alkaline media as [Ru(H2O)6] 3+ have been reported [24]. The oxidation reaction between CMP and permanganate in existance of Ru(III) chloride has stoichiometry of 1:4 with unit order dependence on permangate and Ru(III) and fraction order dependance on base and CMP, which indicates the formation of MnO4•OH 2-, it is further supported by the plot [Ru(III)]/kobs vs. 1/[OH -] with positive intercept.…”
Section: Effect Of 1-[(4-chlorophenyl)methyl]piperidin-4-aminementioning
confidence: 99%